Proposta de um programa de reabilitação auditiva e cognitiva em idosos usuários de auxiliares de audição: estudo piloto - Magrini, Amanda Monteiro (2014)
Hearing loss due to aging involves cognitive, psychosocial and physiological changes in the elderly. Objective: to describe and apply a hearing/cognitive rehabilitation program for elderly hearing aid first users. Method: descriptive, exploratory design research, with longitudinal case study. The sample was composed of six participants, with bilateral sensorineural hearing loss, mild to moderate grade, first users of hearing aid, distributed in two groups: GMCR-conducted auditory cognitive training/with background noise and GMSRconducted auditory cognitive training/without background noise. All participated four training sessions that began after the adaptation of the hearing aid. All have been assessed by means of tests of recognition of sentences with and without the presence of background noise, selfassessment questionnaire of auditory handicap for elderly (HHIE-S), at the beginning and at the end of the auditory/cognitive training program. In the training were emphasized the following activities: evocation, selective attention/attention, auditory and visual synthesis analysis, figure/background visual and auditory, rhyme, rhythm, decoding and encoding graphics, comprehension, logical reasoning and memory. Results: In the GMCR two subjects show improvement in tests of recognition of sentences in noise (LRSR) and silence (SRTS). Only one subject presented benefit at recognition index of sentences in noise (IRSR) and without noise (IRSS). In the GMSR two participants showed improvement in the SRTS with decreased loudness. The more types of errors presented in the two groups were: semantic changes, partial omission and total omission. Conclusion: all participants showed improvement in auditory handicap and GMCR presented a greater benefit than GMSR. The auditory/cognitive training proposal showed that training with noise background may be a successful strategy for the most common claim of elderly listening in-noise